The Role of Creative Self-Efficacy as a Mediator Between Transformational Leadership and Innovative Work Behavior in Food and Beverage SMEs in Malang City - Ahmad Nizar Yogatama (PT. Karya Inovatif Nusantara, 2025)
This study investigates the role of Creative Self-Efficacy (CSE) as a mediator in the relationship between Transformational Leadership (TL) and Innovative Work Behavior (IWB) within food and beverage SMEs in Malang City. A quantitative approach was employed, utilizing structured questionnaires distributed to employees and managers. Data were analyzed using multiple regression and mediation analyses. Results indicate that TL positively and significantly influences IWB both directly and indirectly through CSE. The findings demonstrate that transformational leaders not only inspire employees to innovate but also enhance their confidence in generating creative ideas. The model exhibits excellent fit indices, reinforcing the validity of these relationships. Practical implications include the need for leadership development programs and organizational initiatives that foster CSE to drive innovation. This study contributes to the literature on leadership and innovation in SMEs, particularly within the food and beverage sector.